Aplikasi Tepung Cacing Tanah (Lumbricus rubellus) Untuk Meningkatkan Kadar Omega-3 Dan Omega-6 Ikan Bandeng (Chanos chanos) Budidaya Tambak - Ismail Marzuki; Irwan Paserangi; Muhammad Yusuf Ali (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2020)
The quality of milkfish (Chanos chanos) in ponds cultivation is low. Small body size, pale body surface, odor of mud and low nutritional value cause not compete in the retail market, due to ponds experiencing burnout due to excessive use of synthetic fertilizers and pesticides. The aim of this study was improved the quality of milkfish farming with earthworm flour (Lumbricus rubellus) (TCT). Adding TCT to feed with four different treatments for 30 days. The results showed that the administration of 5%, 10% and 15% TCT, could improve the quality of milkfish ponds, both qualitative and quantitative. Qualitative improvement aspects, namely the surface of the fish's body was brighter, scales cleaner and whiter, the smell of mud was not felt, while the achievement of quantitative aspects was the fish's weight increased sharply in the range of 1.465% - 1.846% per day and omega-3 levels increased in the range of 1.9834 % - 5,5693% and omega-6 increased in the range of 1.4993% - 4.8796% or an increased of nearly 10 times each compared to levels of omega-3 and omega-6 milkfish samples without TCT